The Model Matching Problem for Switching Max-Plus Systems: a Geometric Approach. Issue 40 (2022) - Animobono, D.; Scaradozzi, D.; Zattoni, E.; Perdon, A.M.; Conte, G.
Abstract: Linear systems over the max-plus algebra can model discrete event systems where synchronization, without competition, is involved. The lack of competition can be partly circumvented by considering multiple linear models, each representing a possible choice in resource allocation, and a switching mechanism, thus obtaining a switching linear max-plus system. We propose a formulation of the model matching problem for systems of such kind. The aim is to force a given plant to match exactly the output of a given model. A sufficient condition for the solvability of the problem is obtained by extending the geometric approach to switching systems over the max-plus algebra.